Inertial analysis of acceleration, deceleration, and angular speed in the technical of the front tucked somersault in female artistic gymnastics - Izzo, R.; Biancalana, V.; Ubertini, S.; Cejudo, A.; Cruciani, A.; Hosseini Varde'i, H.; Crudelini, E. (Journal of Physical Education and Sport, 2024)
The aim of this study is to characterize the physical attributes of specific sports movements such as those in women's artistic gymnastics, using objective parameters derived from advanced inertial sensors. A key focus of this research is to establish the validity, reliability, and reproducibility of data acquired through state-of-the-art inertial instruments such as K-Track (K-Sport, Italy). The study focused on elements defined as performance determining, such as acceleration, deceleration, and angular speed in the dynamics of the technical gesture, in this case, the "front tucked somersault" in female artistic gymnastics. Aiming for a more detailed study, the technical act in question was broken down into its three constituent phases: the first and third phases (detachment-ascent and descent-landing of the jump) basically related to a brush leap and the second phase (the frontal turn) to a forward flip. The data obtained from the brush leap confirmed what was expected from an early analysis with the naked eye: significant upward and forward acceleration and development of the jump itself in height and length. On the other hand, with regard to the forward flip, i.e., a forward roll around the transverse axis, after a body tuck-up, we detected rotations around the y-axis that were not expected to be observed, at least with the gyroscope-determined performances, concerning a distinct rotation on the longitudinal axis.